PERLINDUNGAN HUKUM BAGI INVESTOR TERHADAP PENGAMBILALIHAN PERUSAHAAN PENANAMAN MODAL ASING DI INDONESIA - Wisnu Pradiptha, I Gusti Made; Westra, I Ketut; Purwanti, Ni Putu (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013)
Foreign investment is individual foreigner, foreign entities, and / or foreign government investments in the territory of the Republic of Indonesia. In Indonesia, foreign investors shall be in the form of Limited Liability Company under the laws of Indonesia and domiciled in the territory of the Republic of Indonesia, unless other determined by law. Then any foreign companies investing in Indonesia must do business working with the Indonesian company, and then into a new company which is subject to the laws of Indonesia. Therefore, this article will explain whether the Indonesian government is justified in taking a foreign investment company, and explained the legal protection against expropriation of foreign investment companies.
Keywords: Foreign Investment, Acquisition, Company